Propagation strategies for conservation and commercial development of root medicinal crops: A review (Indian Journal of Arid Horticulture, 2025)
India is one of the megadiversity regions endowed with a rich array of medicinal plants. However, the surging demand for herbal medicines has triggered destructive harvesting methods, jeopardizing the natural populations of these plants. Medicinal crops such as ashwagandha, mulethi, and shatavari are globally sought-after due to their therapeutic potential, addressing stress relief, immune function, and hormonal balance. Despite their historical use as natural remedies, the escalating demand is primarily met by wild populations, endangering the survival of these species. The alarming rate of over-exploitation necessitates the development of efficient propagation protocols. This ensures planting material for commercial cultivation and contributes to conservation efforts. Moreover, the cultivation of high-value medicinal plants is creating a new dimension in the field of agriculture, propelling the Indian herbal industry into a flourishing stage. However, the intricate nature of medicinal plant cultivation poses challenges, particularly due to limited knowledge of seed biology. This review concentrates on ashwagandha, mulethi, and shatavari cultivation practices, compiling existing literature to serve as a guide for future research in this crucial field.
Keywords: Ayurvedic formulations; germplasm conservation; herbal medicine; in vitro propagation; tuber